2009
DOI: 10.1021/om800950g
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of a Chemically Non-innocent Acetate Ligand in the Synthesis and Reactivity of Ruthenium Vinylidene Complexes

Abstract: Reaction of the ruthenium bis-acetate complex cis-Ru(κ2-OAc)2(PPh3)2 with a range of terminal alkynes HCCR (R = Ph, CO2Me, C{OH}Ph2, C{OH}Me2) results in the formation of the vinylidene complexes Ru(κ2-OAc)(κ1-OAc)(CCHR)(PPh3)2. The acetate ligands in these species are fluxional and, in the case where R = Ph, are undergoing fast exchange on the NMR time scale even at 195 K. In the case of the hydroxy-substituted complex Ru(κ2-OAc)(κ1-OAc)(CCHC{OH}Ph2)(PPh3)2 a hydrogen bond exists between the OH group on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 94 publications
5
41
0
Order By: Relevance
“…The 13 C{ 1 H} NMR spectra also showed the presence of a single carbonyl resonance for the O 2 CPh groups, consistent with exchange of k 1 -and k 2 -bound benzoate which is fast on the NMR timescale. A similar observation was made for the acetate-containing analogues [16].…”
Section: Stoichiometric Studiessupporting
confidence: 79%
See 3 more Smart Citations
“…The 13 C{ 1 H} NMR spectra also showed the presence of a single carbonyl resonance for the O 2 CPh groups, consistent with exchange of k 1 -and k 2 -bound benzoate which is fast on the NMR timescale. A similar observation was made for the acetate-containing analogues [16].…”
Section: Stoichiometric Studiessupporting
confidence: 79%
“…In addition, we have also demonstrated that hydroxy-substituted vinylidene complexes such as 5b convert to [Ru(k 2 -O 2 CMe)(k 1 -O 2 CMe)(CO)(PPh 3 ) 2 ], 10a and H 2 C]CMe 2 which provides an alternative source of CO in the reaction mixture [16]. These pathways are all plausible routes to the observed carbonyl complexes obtained from the catalytic reaction mixtures.…”
Section: Stoichiometric Studiesmentioning
confidence: 65%
See 2 more Smart Citations
“…Ru ( [Ru(OAc) 2 (PPh 3 ) 2 ]( 4) [16] emerged as most effective (entries 1-9), interestingly,f eaturing the first arene-ligand-free remote CÀH alkylation [17] by ruthenium catalysis. Control experimentsv erified the essential role of the ruthenium catalyst and the base (entries 10 and 11).…”
mentioning
confidence: 99%